2011
DOI: 10.7150/ijms.8.635
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Aspergillus Cerebellar Abscesses in a Middle-Aged Female: Case Report and Literature Review

Abstract: Aspergillus abscesses in the cerebellum are extremely rare, and most cases are solitary. Here, we report the first case of multiple Aspergillus cerebellar abscesses in a 46-year-old female after one mastoidectomy, two craniectomies, and extended use of antibiotics. The possible pathogenesis of this unusual event is discussed. Good outcome was achieved by treatment with a combination of neurosurgical resection and voriconazole (VRC) administration, which we suggest is a potential management plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…Antifungal therapy alone reportedly has a poor outcome for patients with CNS aspergillosis, with a high mortality rate of >90%; this is likely due to the poor penetration of the CNS by the antifungal drugs. 2 Other research has indicated that surgical resection of focal CNS aspergillosis lesions reduces the mortality rate from 64% to 39%. 2 Overall, voriconazole seems to be the drug of choice for the treatment of aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Antifungal therapy alone reportedly has a poor outcome for patients with CNS aspergillosis, with a high mortality rate of >90%; this is likely due to the poor penetration of the CNS by the antifungal drugs. 2 Other research has indicated that surgical resection of focal CNS aspergillosis lesions reduces the mortality rate from 64% to 39%. 2 Overall, voriconazole seems to be the drug of choice for the treatment of aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Other research has indicated that surgical resection of focal CNS aspergillosis lesions reduces the mortality rate from 64% to 39%. 2 Overall, voriconazole seems to be the drug of choice for the treatment of aspergillosis. 2 In the current case, the patient showed clinical and radiological improvement with intravenous voriconazole administration and surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nearly 185 Aspergillus species, A. fumigatus is the most prevalent pathogen, and accounts for more than 90% of all infections reported (Chen et al, 2011). The incidence of invasive aspergillosis occurs in 1 to 8% of liver transplant recipients and the mortality rate ranges from 60 to 80% (Fortún et al, 2002;Singh and Paterson, 2005).…”
Section: Introductionmentioning
confidence: 99%